2018
DOI: 10.1002/jcp.26619
|View full text |Cite
|
Sign up to set email alerts
|

NOTCH4 regulates colorectal cancer proliferation, invasiveness, and determines clinical outcome of patients

Abstract: Notch signal has complex roles in human malignancies, which might be attributed to the diversity of Notch receptors. Here, we set out to identify the association of NOTCH4 with colorectal cancer (CRC). In the hospital-based study cohort, we investigated NOTCH4 mRNA levels in primary CRC, as well as its association with clinicopathologic characteristics. Besides, NOTCH4 cDNA and siRNA was transfected into colorectal cancer cell line to elucidate its impact on tumor cell proliferation and migration. Results reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 39 publications
(58 reference statements)
0
12
0
Order By: Relevance
“…To date, four Notch receptors (Notch 1, Notch 2, Notch 3, and Notch 4) have been identified in mammals [ 5 ]. Notch signaling critically affects the tumorigenesis and proliferation control of cells in the gastrointestinal tract [ 6 ]. It is interesting to note that Notch signaling acts as an oncogenic event in some cancers and a cancer suppressor in others.…”
Section: Introductionmentioning
confidence: 99%
“…To date, four Notch receptors (Notch 1, Notch 2, Notch 3, and Notch 4) have been identified in mammals [ 5 ]. Notch signaling critically affects the tumorigenesis and proliferation control of cells in the gastrointestinal tract [ 6 ]. It is interesting to note that Notch signaling acts as an oncogenic event in some cancers and a cancer suppressor in others.…”
Section: Introductionmentioning
confidence: 99%
“…As a biomarker in many tumors, NOTCH4 established significant roles in cell growth, invasion and apoptosis. Zhang et al (28) revealed that suppressing the expression of NOTCH4 could inhibit the PCa progression and epithelialmesenchymal transition by stimulating NF-κB. Regarding MAL (29), it was reported that low expression of MAL was associated with poor failure-free survival and it might serve as an independent prognostic signature when estimating the tumor immune infiltrate in classical Hodgkin lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has illustrated the specificity of NOTCH4 for different cancers and has suggested the potential for NOTCH4 to be used as a marker for the diagnosis and prognosis of cancers. Zhang et al15 reported that NOTCH4 might be an independent marker of relapse and prognosis in colorectal cancer patients, because overexpression of NOTCH4 in colorectal cancer cell lines suppressed tumor cell proliferation, migration, and invasion, while it induced apoptosis. Consistent with colorectal cancer, previous results demonstrated that high expression of NOTCH4 in ovarian cancer is correlated with a better prognosis 27,28.…”
Section: Discussionmentioning
confidence: 99%
“…As one of the main signaling pathways of cancer stem cells, the NOTCH signaling pathway plays an important role in the maintenance of self-renewal, multidirectional differentiation, and apoptosis of various cancer stem cells and thus participates in the regulation of cancer stem cells 13. Deregulation or mutation of NOTCH receptors, ligands, and signaling regulators is implicated in the occurrence, development, and progression of several human solid tumors, for example, breast cancer,14 colon cancer,15 and liver cancer,16 as well as NSCLC 17. Previous reports have demonstrated that NOTCH signaling is activated aberrantly and plays a critical role in the initiation, progression, and metastasis of NSCLC 18…”
Section: Introductionmentioning
confidence: 99%